Analisis Problem Solving Skills Siswa pada Materi Lingkungan - Nadya Utari; Nur Eka Kusuma Hindrasti; Trisna Amelia (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
The purpose of the research was to find out the level of the students' problem solving skills on environmental material at X class of MAN Bintan. The researcher applied descriptive quantitative approach as method for analyzing the data. Sampling in this study using Total Sampling technique with the sampel consisted of 59 students. This instrument is used to collect students' problem solving skills through six aspects to Chang & Kelly with 6 items essay and feature interviews. The data were analyzed with statistical rule in percentage. Based on the results of data analyze shows that a 77% rate highly classified. The researcher concluded that student at X class MAN Bintan has good problem solving skills. However, it still needs training and guidance to develop problem solving skills.